Enzyme activities in cocoa beans during fermentation - Hansen, C.E.; Olmo, M.; Burri, Ch.
The activities of endoprotease, aminopeptidase, carboxypeptidase, invertase (cotyledon and pulp), polyphenol oxidase and glycosidases were studied during heap fermentation of ICS-95 cocoa beans. These enzymes are of key importance in flavour precursor formation and in pigment degradation during cocoa fermentation. Optimal extraction and assay conditions were established to characterise the enzymes reactions and to quantify and compare enzyme activities during cocoa fermentation. The enzymes exhibited large differences in pH optima and stability during fermentation. Aminopeptidase, invertase (cotyledon and pulp)and polyphenol oxidase were strongly inactivated, carboxypeptidase was partly inactivated, whereas endoprotease and glycosidases remained active throughout the fermentation. Since many enzymes are inactivated during fermentation, it is generally recognised that the actual period of enzyme action is short. Although our results confirmed total inactivation for some enzymes, we show that several key enzymes are not completely inactivated during fermentation. Therefore, some enzyme reactions can continue throughout the whole fermentation process. Only polyphenol oxidase was strongly inactivated during sun and artificial drying of the beans. The other enzymes were stable during the drying process. Enzymes like endoprotease and glycosidases are still active in properly fermented and dried beans.
Keywords: AMINO ACID; COCOA; ENZYME; FERMENTATION; FLAVOUR; GLYCOSIDASE; INVERTASE; PEPTIDE; PEPTIDASE; POLYPHENOL OXIDASE; PROTEASE; SUGAR